Essay on reparation for victims of armed in Colombia (2012)
This essay is to help its readers to have a reflection on the right to the truth that the victims of the Colombian conflict have in the context of transitional justice. The essay began conceptualizing this kind of justice. In this paper, we highlight the role of truth commission in the repair process. Similarly, as part of this study, an analysis of the importance of clarifying the truth and the means available for its realization is made, always within the specific framework of the Justice and Peace Law. Finally, this paper concludes that the establishment of the truth is one of the major weaknesses that transitional justice in Colombia has to deal.